Relations between Iron Deficiency Anemia and Anemia from Hookworms Parasites: Eman Hussein Jafer, Jamal A. AL Jabbar Attawi and Taghreed khudhur Mohammad - AL Jabbar Attawi, Jamal A. (The Iraqi Journal of Veterinary Medicine, 2015)
This research aimed at identifying the relationship of iron-deficiency anemia caused by insufficient dietary intake and the iron-deficiency anemia caused by parasitic worms such as hookworms. Whole blood was drawn from 40 specimens; 20 males and 20 females, normal healthy controls with age ranges 8-50 year. Blood samples were collected from 80 patients with symptoms of anemia, with age range from 10-50 year. After fecal examination, they were divided into two groups: Group one, iron-deficiency anemia with non-parasitic; and group two, iron-deficiency anemia with parasitic. Blood samples were divided into two container, one for the hemoglobin, other for serum ferritin and elements of iron, zinc in tubes without anticoagulants. Results demonstrated a significant decrease in the levels of serum iron, serum ferritin, and hemoglobin in male and female patients (in group one without parasitic worms) as compared with control groups. Furthermore (in two groups with and without parasitic worms), a significant decrease in the level of serum zinc in male and female patients as compared with control group. A significant decrease in the levels of serum iron, ferritin and hemoglobin were observed in male and female patients with iron-deficiency anemia caused by parasitic hookworms compared with control group. The worm burden was classified as light, moderate and heavy as estimated by egg counts per gram of faeces, so results showed the median increase with developing of iron deficiency anemia from parasitic hookworms.